PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PADA KOPERASI SERBA USAHA (KSU) SIDI SANUR - Ni Luh Ayu Meilan Sulasmini; Ni Nyoman Suryani; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Job satisfaction is a pleasant psychological state felt by workers in a work environment due to adequate fulfillment of needs. Someone who has high job satisfaction will have attitudes that reflect his work, such as arriving on time, always being tenacious and active at work, respecting his superiors. Job satisfaction is an employee's pleasure in his job and position in the company. This study aims to determine the effect of compensation, motivation and work discipline on job satisfaction at the SIDI Sanur Multi-Business Cooperative (KSU). Methods Data collection was carried out by observing and using a questionnaire. The population of this study were employees of the SIDI Sanur multi-business cooperative (KSU). The sample in this study was 45 respondents using Non Probability Sampling which was selected by saturated sampling (census). The data analysis technique used is multiple linear regression analysis using IBM SPSS 25 software. The instrument test results show valid and reliable data. The results showed that (1) compensation had a positive and significant effect on job satisfaction, (2) motivation had a positive and significant effect on job satisfaction, (3) work discipline had a positive and significant effect on job satisfaction.